Marketingové plánování současných a potenciálních oborů podnikání jako subsystém strategického managementu podniků chemického průmyslu - Lošťáková, Hana (Univerzita Pardubice, 1999)
This paper deals with position of marketing planning of current and potential SBUs in system of strategic management of chemical companies. It discuses qualification of top management and management of SBUs in this system. It also shows the succession of phase of strategic management process with marketing planning of SBUs as its subsystem.
Keywords: chemický průmysl; podniky; Marketing; Strategický management